Respostas
respondido por:
2
4x+3y=12
y = - 6
Substituindo y
4x + 3*-6 = 12
4x - 18 = 12
4x = 12 + 18
4x = 30
x = 30 / 4 Simplificando por 2
x = 15 / 2
Resposta: 15/2 ou decimal 7,5
y = - 6
Substituindo y
4x + 3*-6 = 12
4x - 18 = 12
4x = 12 + 18
4x = 30
x = 30 / 4 Simplificando por 2
x = 15 / 2
Resposta: 15/2 ou decimal 7,5
respondido por:
1
4x+3y=12. se y= -6 temos
4x+3(-6)=12
4x-18=12
4x=12+18
4x=30
x=7,5
Obs: lembre se que (+) com (-)= (-)
4x+3(-6)=12
4x-18=12
4x=12+18
4x=30
x=7,5
Obs: lembre se que (+) com (-)= (-)
thays283:
obrr
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás